Course and outcomes of pregnancy in women treated for acromegaly: Discerning a contemporary cohort. (October 2021) - Das, Liza; Dutta, Pinaki; Thirunavukkarasu, Balamurugan; Gupta, Kirti; Tripathi, Manjul; Gupta, Prakamya; Aggarwal, Neelam; Rai, Ashutosh; Radotra, Bishan Dass; Bhansali, Anil; Suri, Vanita
Abstract: Objective: To analyze pregnancy course and outcomes in women treated for acromegaly and compare outcomes based on disease activity at the time of conception. Design: Retrospective study. Patients: Women with acromegaly diagnosed prior to or during pregnancy from 2010 to 2019, representing cases (14 pregnancies in 12 cases), were later stratified based on active ( n  = 5) or controlled disease ( n  = 9) at time of conception. Female acromegalic patients over the same period constituted the 'acromegaly cohort' (AC) ( n  = 75). Results: All cases had macroadenomas with nadir GH of 15.06 ng/ml (IQR 9–30), IGF-I index of 3.04 (1.96–3.82), for which they had undergone pituitary surgery; except two patients diagnosed during pregnancy, who received pharmacotherapy followed by surgery 4 months postpartum. Adjuvant pharmacotherapy was required in 71.4% patients and radiotherapy in 35.7%. Pregnancy occurred at a median of 2 (0.8–5.1) years after surgery and 21.4% required assisted reproduction. All had term delivery with normal APGAR except one case with gestational hypertension, who delivered a preterm baby. None had congenital malformations. Despite higher baseline IGF-I, GH and tumor volume in those with pre-conceptional active acromegaly, materno-fetal outcomes were not different from those with controlled disease ( p  > 0.05). Similar or greater proportion of cases had normal GH and no residual tumor postpartum, even in those with pre-conceptional active acromegaly. Conclusion: The current study showed conducive outcomes of gestation in women treated for acromegaly and no higher rates of pregnancy parameters or complications than non-acromegaly pregnancies in the same population. Active acromegaly does not seem to have an adverse bearing on outcomes. Highlights: Acromegaly has customarily been associated with subfertility and adverse gestational outcomes. In the current study, gestational complications in acromegaly pregnancies were comparable to non-acromegaly pregnancies. Materno-fetal complications were not higher in those with active disease at conception. Acromegaly in pregnancy may even show spontaneous remission following delivery.